Sustainable Control Tactics of the Cereal Leafminer Syringopais Temperatella Led. (Lep., Scythrididae) in Jordan: Resistant Cultivars and Combined Use of Tillage and Insecticides - Shawawreh, M; Al-Zyoud, Firas; Shakhatreh, Y. (Jordan Journal of Agricultural Sciences, 2022)
The cereal leafminer, Syringopais temperatella Led. (Lep., Scythrididae) is considered one of the most serious insect pests that infests wheat in the field, and causes economic damages to the crop in Jordan. However, little attention has been paid to the susceptibility of common wheat cultivars and no attention has been paid to the combined use of tillage regime and insecticides against S. temperatella. Concomitan tly, this study aimed at investigating the susceptibility of the most commonly grown wheat cultivars in Jordan to S. temperatella under field conditions, and the effect of the combined use of tillage regime and insecticide applications in controlling the pest on wheat. The 1st experiment was set up to determine the susceptibility of four common wheat cultivars to the pest in the 2016/2017 cropping season, while the 2nd one was set up to investigate the effect of the combined use of tillage regime and insecticides against the pest in 2017/2018 cropping season in Al-Qasr, Karak. Four common wheat cultivars (Deer Alla, Em-Qees, Sham, and Horani 27), were used in the 1st experiment, while in the 2nd experiment, 6 different treatments were done using the wheat cultivar, Horani 27, namely, T1: no-tillage, T2: deep plowing in summer, T3: deep plowing in summer and treating seeds with diazinon, T4: chisel plow at seed sowing time with treating seeds with diazinon, T5: no-tillage and treating seeds with diazinon, and T6: chisel plow at seed sowing time. In the two experiments, data on larvae number, infestation, grain and straw weights, and plant height were recorded. Results showed that infestation and larvae numbers were the lowest, and grain and straw weights were the highest in Horani 27 compared to other cultivars. Data showed that the lowest infestation and larvae number were obtained in the no-tillage, and grain and straw weights were the highest in deep plowing in summer and treating seeds with diazinon. While the tallest plant was recorded in deep plowing in summer and deep plowing in summer by treating seeds with diazinon. In conclusion, Horani 27 is the least susceptible cultivar to the pest, and no-tillage reduces larvae number and infestation while plowing in summer by treating seeds with diazinon increased yield and strawweight, and plant height.